Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant

Study of magnetism and electrocatalytic properties in perovskite DyCrO3 - Ughade, Supriya; Singh, Dinesh; Poddar, Pankaj (Journal of Alloys and Compounds, 2025)
Uniformly sized perovskite DyCrO3 was synthesized by facile hydrothermal method. Complex interdependence of various parameters such as - pH, crystal growth duration, reaction temperature, precursor, and capping molecules on crystal growth was extensively investigated. The effect of synthesis parameters on the magnetic properties of hydrothermally synthesized DyCrO3 was compared with high-temperature synthesized DyCrO3. DyCrO3's potential for electrocatalytic water splitting in an alkaline medium (1.0 M KOH) was also evaluated. It demonstrates an overpotential of 280 mV for oxygen evolution reaction (OER) and 210 mV for hydrogen evolution reaction (HER). Further, it exhibits promising stability for OER and HER.
Keywords: DyCrO3; Electrocatalytic water splitting; Hydrothermal synthesis; magnetic property; perovskite